XBRL formula specification in the multidimensional data model. (April 2016) - Santos, Ignacio; Castro, Elena; Velasco, Manuel
Abstract: XBRL is a specification used to exchange financial/economic information. It is actively used by many international institutions and agencies. In the USA, Canada, Europe, China, etc. all financial entities and companies quoted on the stock market have to report compulsorily to the supervisory and regulatory authority using the XBRL specification. XBRL consists of a set of taxonomies defining different accounting regulations for a specific statement and the statement itself. Reports are generated from various sources and are validated at origin. XBRL displays business information which is multidimensional and whose logical destination for storage is a data warehouse. The proposal presented here focuses on the automation of the mapping between XBRL and the multidimensional data model (MDM) and includes a formalization of the validation rules in the MDM. The approach is designed in accordance with the Model Driven Architecture (MDA) paradigm which consists of a new way to validate XBRL reports through an RDBMS, and offers a proof-of-concept. Additionally, the study aims to provide more clarity about XBRL, a highly complex language made by and for expert users, and to improve interoperability between applications. The proposal also analyses certain semantic questions associated with the XBRL formula specification and its performance. Highlights: Automation of the mapping between XBRL and the multidimensional data model (MDM). Formalization of the validation rules in the MDM. XBRL is a specification used to exchange financial/economic information. The approach is designed in accordance with the Model Driven Architecture (MDA). A new way to validate XBRL reports through an RDBMS, and offers a proof-of-concept.